2004
DOI: 10.1117/12.512731
|View full text |Cite
|
Sign up to set email alerts
|

Thermal management of LEDs: package to system

Abstract: Light emitting diodes, LEDs, historically have been used for indicators and produced low amounts of heat. The introduction of high brightness LEDs with white light and monochromatic colors have led to a movement towards general illumination. The increased electrical currents used to drive the LEDs have focused more attention on the thermal paths in the developments of LED power packaging. The luminous efficiency of LEDs is soon expected to reach over 80 lumens/W, this is approximately 6 times the efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
97
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(101 citation statements)
references
References 6 publications
0
97
0
4
Order By: Relevance
“…Recently, high-power GaN-based LEDs have attracted much attention and are considered candidates for next-generation general illumination applications due to their high luminous efficiency, long operating life, energy savings, and so forth. 1 However, a power saturation phenomenon 2 was often encountered in the operation of GaN-based LEDs packaged with silver paste when the current injection level was raised. This is because the thermal conductivity of silver paste is poor and the heat generated from LEDs was not being efficiently dissipated, resulting in reduced conversion efficiency with increasing junction temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, high-power GaN-based LEDs have attracted much attention and are considered candidates for next-generation general illumination applications due to their high luminous efficiency, long operating life, energy savings, and so forth. 1 However, a power saturation phenomenon 2 was often encountered in the operation of GaN-based LEDs packaged with silver paste when the current injection level was raised. This is because the thermal conductivity of silver paste is poor and the heat generated from LEDs was not being efficiently dissipated, resulting in reduced conversion efficiency with increasing junction temperature.…”
Section: Introductionmentioning
confidence: 99%
“…With the use of large LED arrays, it is possible to generate a large heat loads at the system level which can cause challenges for overall heat dissipation, especially when passive cooling is used. The large array with passive cooling techniques leads to elevated LED die temperatures, which have been linked to lower quantum efficiencies, shorter lifetimes, emission wavelength shifts and, catastrophic device failure [1][2][3][4][5][6]. A heat flux from a 900 high brightness LED chip, has already reached approximately 125 / [3] which is considered relatively high heat flux and comparable to heat generation in integrated circuits.…”
Section: Introductionmentioning
confidence: 99%
“…As a rule, their functional loss is a consequence of overloads, short circuits and deformations [1]. The processes regularities analysis allows making a conclusion describing, first of all, a regulation conditions disruption of LED heat exchange with the environment and, as a result of it, the LED fails [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The balanced models and software applications based on them (the LED's thermal resistance calculation models [2], taking into account the infrared radiation effects [6], p-n junction temperature change [4], as well as CFD-simulation [7]) are the mostly widely used. However, many experiments [3,5,6,8,9] with different LEDs showed that the balanced models application domain is very limited.…”
Section: Introductionmentioning
confidence: 99%